Among Leonine, Draconian and Humanoid Shapes: Notations on the Pictorial Representation of Beasts and Devils in the Castilian and Aragonese Areas (12th-13th Centuries) - Consiglieri, Nadia Mariana (Eikón / Imago, 2016)
In this paper we will analyze the iconographic and pictorial ties between beasts and devils represented in different visual materialities belonging to the Castilian and Aragonese areas during the 12th and 13th centuries. In miniatures of the Rylands Beatus, in wall paintings of San Pedro de Arlanza’s Monastery, in the front altar panel of the Archangels and in the San Martín de Chía’s one there are represented diverse evil characters which have a strong corporeal hybridity. The leonine and draconian fierceness of certain beasts alludes to the classical chimera; attributes transmitted also for the depiction of the devil though with anthropomorphous features. This way, we will perform a dynamic dialog between these images and different iconographic survivals that works in the visual rhetoric demonology of the plenary Hispanic Romanesque and the called style of 1200.